‘Bloomify™ Red’ and ‘Bloomify™ Rose’, Two Infertile Lantana camara Cultivars for Production and Use in Florida - Zhanao Deng; Sandra Barbour Wilson (EDIS)
'Bloomify™ Red’ and ‘Bloomify™ Rose’ are two new infertile Lantana camara cultivars that have been developed as alternative to the invasive forms of this species, a Category I invasive species in Florida. Both cultivars have been trialed and tested in Florida and reviewed by the IFAS Invasive Plants Working Group, which concluded that the two cultivars are “not a problem species”. In 2016, the IFAS Cultivar Release Committee approved the release of these cultivars. A plant patent application has been filed for each of the new cultivars under their code name (‘UF-1013A-2A’ and ‘UF-1011-2’). The Florida Foundation Seed Producers, Inc. has awarded an exclusive license to Ball Horticultural Company for propagation and/or production. This publication describes the plant, stem, leaf and flower characteristics, and the male and female infertility of these new cultivars, and their hybridization potential with Lantana depressa, the Florida native lantana species.